First study using a fixed-wing drone for systematic measurements of aerosol vertical distribution close to a civil airport - Harm-Altstädter, Barbara; Voß, Anna; Aust, Sebastian; Bärfuss, Konrad; Bretschneider, Lutz; Merkel, Maik; Pätzold, Falk; Schlerf, Andreas; Weinhold, Kay; Wiedensohler, Alfred; Winkler, Ulf; Lampert, Astrid (Frontiers in Environmental Science, 2024)
A profound knowledge of pollutant emissions and transport processes is essential to better assess the impact on local air quality, which ultimately affects human health. This is of special importance in the proximity of airports, as flight activities are a major source of ultrafine aerosol particles (UFP) that are associated with adverse health effects. A quantification of the aerosol population in the horizontal and in particular in the vertical distribution has not been sufficiently characterized so far, but is of crucial relevance, as the atmospheric boundary layer (ABL) is strongly interacting with aerosols. For this purpose, the fixed-wing research drone called ALADINA (Application of Light-weight Aircraft for Detecting IN-situ Aerosol) was operated at a distance of approximately 4 km downwind of the German airport Berlin Brandenburg (BER) on October 11-19, 2021. During the investigation period, 140 vertical profiles of different meteorological parameters and aerosol particle sizes were obtained on six measurement days between the surface and up to a maximum altitude of 750 m above ground level (a.g.l.). The investigations indicate several features: The stability of the ABL is a key characteristic for the vertical distribution of aerosol population with highest concentrations close to ground. Inversion layers further enhance horizontal transport so that airport pollutants can be moved to a further distance away. The airborne observations of total particle number concentration (TNC) coincide with ground-based data from fix-point sites. They show a high variability depending on the distance to the plume as well as upwind position and highest concentrations of TNC related to rush hours of airport operations.